New species and records of Ammobatine bees from Pakistan, Kyrgyzstan, and Sri Lanka (Hymenoptera: Apidae) - Engel, Michael S. (Acta entomologica slovenica (Ljubljana), 2008)
Four new cleptoparasitic bees of the tribe Ammobatini (Apidae: Nomadinae) are described and figured from southeastern Pakistan and Sri Lanka. Ammobates maxschwarzi sp. n. (Pakistan) is known from a series of females, while A. cinnamomeus sp. n. (Pakistan), Parammobatodes craterus sp. n. (Pakistan), and Chiasmognathus taprobanicola sp. n. (Sri Lanka) are known from males and females. The species are distinguished from their congeners and comments madeon potential hosts. In addition, C. gussakovskii (Popov), previously known only from Tajikistan, is newly recorded from southern Kyrgyzstan.
Keywords: čebele; entomologija; Hymenoptera; Kirgizistan; Kyrgyzstan; nove vrste; Pakistan; Šri Lanka